KEANEKARAGAMAN JENIS REPTIL ORDO SQUAMATA DIKAWASAN HUTAN LINDUNG GUNUNG SEMAHUNG DESA SEBATIH KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Amri, Syaiful; Nurdjali, Bachrun; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2015)
ABSTRACT Reptiles are one species of fauna mostly found in West Kalimantan. This research aims to investigate kinds of squamates living in the area of Semahung mountain protected forest in Sebatih village in Sengah Temila sub-district in Landak district. Thhe research took place from February 14th to March 1st 2014 using visual encounter survey (VES). The status squamates found based on the red list of IUCN (International Unio for Conservation of Nature and Natural Resources) comprises ten least concern squamates, two near threatened squamates and two not evaluated squamates. There are forteen species of squamates from five families. Based on Percent Similary value evaluation, the highest abundance is from Scincidae family that isÂ  Eutropis rudis of 37%. The highest diversity value is on aquatic habitat of eâ€™=0,8019. Of two habitats (aquatict and terrestrial) of squamates, the similary index of two habitats is 0,4, meaning that there are 40% of those species living in those habitats are similar species and 60% of those are different. It is because the two habitats have the similar altitude. Eutropis rudis have the highest meeting probability of 0,486 individual/hour. They are mostly seen in terrestrial habitat. Keywords: Squamates, species diversity, Semahung Mountain